The role of information and communication technologies in supply chains efficiency in COVID-19 pandemic - R. S. Rogulin (Управление)
Information and communication technologies have become an integral part of our life. Supply chain management is also currently in a digital transformation, especially during the period of disruptions in global and local supply chains caused by the COVID-19 pandemic. The purpose of this study is to provide an empirical descriptive analysis of the role of digital technologies in improving the efficiency and recovery of supply chains, as in the pre-crisis period and in a pandemic.The research is based on the processing of statistical data and macroeconomic indicators, presented in the public domain. The following indicators were considered as basic indicators: gross domestic product as a characteristic of the level of economic development of Russia before the crisis; Logistics efficiency index; Digital Life Index. For comparative analysis, countries from different categories were selected in the context of the selected assessment indicators. The results obtained confirmed the significant role of information and communication technologies in improving the efficiency and restoration of supply chains destroyed in connection with COVID-19 pandemic.It has been concluded that at the national level, developed economies showed high efficiency of their logistics systems and high scores of digital life rating. For countries with a level of economic development below average, the impact of information and communication technologies on the efficiency of the logistics system was not decisive in this context. The implementation of information and communication technologies makes it possible to restore the supply chains destroyed by the crisis and increase their efficiency, because of which a business in a pandemic gets a chance to survive.The results of this study can be used by heads of enterprises of various levels in determining the strategy and tactics of enterprise development, including crisis management. Research methods and data can be applied by researchers to further research into the impact of information and communication technologies on the recovery and efficiency of global and local supply chains, including considering updated data that consider the impact of the coronavirus pandemic on the indicators used in this article.